Pembandaran kolonial & penghapusan bangsa Melayu di Malaysia - Norsaleha Mohd. Salleh; Mohd. Zul Fahmi Md. Bahrudin; Nur Hanis Mohamad Noor (Kuala Lumpur : Interdisciplinary Research and International Strategy (IRIS) Institute Berhad, 2021)
History of colonial urbanization in Malaysia.
Includes bibliographical references.
Keywords: Malays (Asian people) -- Malaysia -- Ethnic identity; Urbanization -- Malaysia; Cities and towns -- Malaysia